Protection of Women's Rights After Divorce in Divorce Lawsuit at the Padang Panjang Religious Court - Ulya, Zakiyah; Endriyanti, Endriyanti (Universitas Islam Negeri Sjech M. Djamil Djambek Bukittinggi, 2023)
Divorce is one of the reasons for the breaking of the binding rope between husband and wife. Divorce occurs due to the disharmony of the relationship between husband and wife in carrying out their rights and obligations in a family. The existence of divorce does not mean the release of the husband's responsibility to provide for the ex-wife. There are still some obligations of the husband to provide for his wife after the breakup of divorce, according to applicable regulations. The rights of wives after divorce are regulated by Law Number 1 of 1974 and the compilation of Islamic law in the form of Iddah, mut'ah, madhiyah, hadhanah, and children. This applies not only to divorce cases but also to lawsuit divorces. The purpose of this study is to determine the judge's decision that accommodates the rights of wives after divorce in divorce cases. As well as what rights are imposed on the husband.Â This research method uses qualitative methods that are more devoted to field research, namely research whose object is a judge's decision that accommodates the rights of wives after divorce in divorce cases. The results showed that out of 237 divorce cases, only 28 rulings gave wives post-divorce rights. The decision of the judge of the Padang Panjang Religious Court regarding women's rights is concluded as follows: (1). There are still divorce cases with vertex judgements that do not contain the rights of wives because the judge only decides cases by the material of the lawsuit, so the judge does not (2).Â Not all divorce cases accommodate claims regarding their rights as wives. Although judges have ex oficio rights in determining the rights of women (wives), whether requested or unsolicited, the judges of the Padang Panjang Religious Court exercise their rights ex oficio to punish husbands for providing iddah, mut'ah, and past income according to ability and eligib ility.Perceraian merupakan salah satu sebab putusnya tali pengikat antara suami dan isteri. Perceraian terjadi akibat tidak harmonisnya hubungan antara suami dan istri dalam menjalankan hak dan kewajibannya di dalam sebuah keluarga. Adanya perceraian bukan berarti lepasnya tanggung jawab suami untuk memberikan nafkah kepada mantan Istri. Masih ada beberapa kewajiban suami untuk memberikan nafkah kepada sang istri pasca putusnya perceraian menurut ketentuan yang berlaku. Hak istri pasca perceraian yang diatur oleh Undang-undang Nomor 1 Tahun 1974 dan kompilasi hukum Islam berupa nafkah Iddah, mut'ah, nafkah madhiyah, hadhanah dan nafkah anak. Hal ini berlaku tidak hanya untuk perkara cerai talak, tetapi juga cerai gugat. Tujuan dari penelitian ini adalah untuk mengetahui keputusan hakim yang mengakomodir hak istri pasca perceraian dalam perkara cerai gugat. Serta hak-hak apa saja yang dibebankan kepada suami. Metode penelitian ini menggunakan metode kualitatif yang lebih dikhususkan pada penelitian lapangan, yaitu penelitian yang objeknya adalah putusan hakim yang mengakomodir hak-hak istri pasca perceraian dalam perkara cerai gugat. Hasil penelitian menunjukkan bahwa dari 237 perkara cerai gugat hanya 28 putusan yang memberikan hak-hak istri pasca perceraian. Putusan hakim Pengadilan Agama Padang Panjang mengenai hak-hak perempuan, disimpulkan sebagai berikut: (1). Kasus perkara cerai gugat dengan putusan verstek masih ada yang tidak memuat hak-hak istri, karena hakim hanya memutuskan perkara sesuai dengan materi gugatan sehingga hakim tidak (2). Kasus perkara cerai gugat belum semua yang mengakomodir gugatan mengenai haknya (istri). Meskipun hakim memiliki hak ex oficio dalam menentukan hak-hak perempuan (istri) baik diminta maupun tidak diminta, namun hakim Pengadilan Agama Padang Panjang menggunakan haknya secara ex oficio menghukum suami untuk memberikan nafkah iddah, mut'ah, dan nafkah lampau sesuai dengan kemampuan dan kelayakan.